Serviços over the top (OTTS) disruptivos e a competição com os serviços tradicionais de telecomunicações que necessitam de outorga estatal para a sua exploração - Ayres, André Pessoa (2021)
This research aims to investigate the debates regarding the competition between over the top services and traditional telecommunications services, considering the regulatory asymmetry that exists between them. The so called over the top are services that can replace or considerably improve a traditional telecommunications service. However, the over the top services are, currently, not subjected to any regulation, whereas traditional telecommunications services suffer from various regulatory burdens. Considering this scenario, this research aims to understand why over the top services are not regulated, having as a start point the attempt to classify them according to the national laws and the General Telecommunications Law, in order to verify if, in theory, their exploitation would require, beforehand, the granting of a State authorization. Taking into account that over the top services are classified as value-added services, which are considered users of traditional telecommunications services, the need to discuss the benefits and harms of its eventual regulation becomes clear. For this reason, two public consultations on the issue were analyzed, as well as two technical studies related to the matter, making it possible to bring to the research the arguments for and against the regulation. Finally, the research focused on a case study about the conditioned access services (SeAC), which are regulated authorized services that suffer strong competition from over the top Video On Demand (sVOD) services, which are, currently, free from regulation. With all the elements above, the deductive research method was utilized to reach the conclusion that over the top services are considered value added services that cannot be confused with traditional telecommunications services, especially because over the top services do not have any control over the infrastructure needed to provide their service. Thus, when it comes to the exploitation of over the top services, the granting of State authorizations is not necessary.